Reducing Marine and Coastal Pollution - World Bank Group (World Bank, Washington, DC, 2016)
The West African coastline is home to major industries, mining activities, peri-urban and agro-industry, and tourism, as well as urban and seaside residences, all of which generate waste and cause pollution. Many areas along the coast also lack adequate wastewater and solid waste management systems. As a result, large volumes of untreated wastewater and solid waste are dumped into the open, polluting the land and water. Water quality studies can help policy makers set targets and baselines and develop pollution reduction plans at the local, national, and regional levels. Such studies generally focus on pollution from sewage/wastewater, nutrients, and marine litter; they may also include other pollutants, such as oil (spills from ships and offshore oil exploration and production), chemicals, and heavy metals. Reducing the generation of plastic debris requires collect¬ing data on the origin, volumes, and types of plastic litter, so that appropriate measures can be taken to reduce the use of, reuse, or recycle plastic products.